The Infulence of Diabetes Self Management Education with AVA on the Knowledge of Diabetes Mellitus Type 2 - Erika Martining Wardani; Riezky Faisal Nugroho (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: High or uncontrolled blood sugar levels are still widely found, one of which is due to the patient's lack of knowledge about the disease, diet and treatment of DM sufferers. Overcoming these problems by providing health education. Diabetes self management education (DSME) is a process to support knowledge, skills and abilities in diabetes self-care. Objective: This study examines the influence of diabetes self management education with ava on the knowledge of diabetes mellitus type 2. Methods: The design of this study used a quasy experiment with a pre-test and post-test nonequivalent control group approach. The population in this study were all elderly people with Diabetes Mellitus as many as 170 people, the sample was 60 respondents who were taken using the simple random sampling technique. The instrument used was a questionnaire given before and after the intervention. Data were analyzed using the Wilcoxon Signed Ranks Test with α = 0.05. Results: The research results obtained that the respondent's knowledge after (post test) giving intervention DSME with AVA obtained a Mean Rank value of 3.00 while the level of knowledge before it was carried out (pre test) obtained a Mean Rank value of 2.50 obtained a Sig value of 0.0001 which means if p